Comparisons of bone mineral density in steroid dependent, frequent relapse, and infrequent relapse nephrotic syndrome children - Lies Dewi Nurmala; Taralan Tambunan; Idham Amir (Paediatrica Indonesiana, 2010)
Background Children with nephrotic syndrome, especially those with steroid dependent and frequent relapse are at greater risk of reduced bone mineral density (BMD).Objective To determine bone mineral density (BMD) in steroid dependent and frequent relapse compared to infrequent relapse nephrotic syndrome.Methods We conducted a cross-sectional study at the Child Health Department, Cipto Mangunkusumo Hospital, from August until November 2009. Subjects were 5 to 18 year-old children with steroid dependent nephrotic syndrome (SDNS), frequent relapsenephrotic syndrome (FRNS), or infrequent relapse nephrotic syndrome (IRNS). Ionized calcium level, vitamin 25(OH)D3 level, and BMD were measured us ng dual energy x-ray absorptiometry (DEXA).Results 11 SDNS and 11 FRNS cbildren (group I) were compared with 22 IRNS children (Group II). Children of SDNS and FRNS had significantly longer duration of illness, more relapses, longer steroid therapy duration, and greater cumulative steroid dose compared to group 11 (IRNS). There were no differences betweenÂ  the two groups with regard to mean ionized calcium level and vitamin 25(OH)D3 level. Children in group I had lower z-scores compared to group lI, but the difference was not statistically significant r mean (SD) -1.182 (1.21) vs. -0.795 (1.25), P=0.305]. Subgroup analysis showed that SDNS children had lower z-scores than FRNS [-1.791 (1.17) vs. -0.57 (0.94), P=0.019] and IRNS [-1.791 (1.17) vs. -0.795 (1.25), P=O.026].Conclusion Children with SDNS have significantly lower BMD z-scores compared to those with FRNS and IRNS.